6(e+1)+3=2e-7

Simple and best practice solution for 6(e+1)+3=2e-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(e+1)+3=2e-7 equation:


Simplifying
6(e + 1) + 3 = 2e + -7

Reorder the terms:
6(1 + e) + 3 = 2e + -7
(1 * 6 + e * 6) + 3 = 2e + -7
(6 + 6e) + 3 = 2e + -7

Reorder the terms:
6 + 3 + 6e = 2e + -7

Combine like terms: 6 + 3 = 9
9 + 6e = 2e + -7

Reorder the terms:
9 + 6e = -7 + 2e

Solving
9 + 6e = -7 + 2e

Solving for variable 'e'.

Move all terms containing e to the left, all other terms to the right.

Add '-2e' to each side of the equation.
9 + 6e + -2e = -7 + 2e + -2e

Combine like terms: 6e + -2e = 4e
9 + 4e = -7 + 2e + -2e

Combine like terms: 2e + -2e = 0
9 + 4e = -7 + 0
9 + 4e = -7

Add '-9' to each side of the equation.
9 + -9 + 4e = -7 + -9

Combine like terms: 9 + -9 = 0
0 + 4e = -7 + -9
4e = -7 + -9

Combine like terms: -7 + -9 = -16
4e = -16

Divide each side by '4'.
e = -4

Simplifying
e = -4

See similar equations:

| 3y+12=-3x | | (25/36)^(-2/3) | | 0.8d=100 | | 414=18.0 | | d*0.8=100 | | u/9=7 | | 6(x-2)=2(-3+3x) | | 4(x+1.82)=3x | | a=wI | | -4x+8=4x-16-8 | | x^4-22x^2+120=0 | | 136.649+16.4+73.18+2.4878= | | 14+86=15 | | z+149.3=73.5633-1.317 | | x+86=15 | | c=8d+30 | | 22+16+19+15+13= | | 73.9+105+108.0359+197.89= | | -4(x+3)=-12-4x | | 10x-10=6x+6 | | 109.598+197-29.7156-32.87= | | 1.25(m-2)=1.50(m-3) | | -8(x-4)=4(8-2x) | | y=0.5x^2-x^3+1 | | 0.6x+11.6=x-1.04 | | -3(x+5)=-60+6x | | 2(3.14)9(9)+2(3.14)9(27)= | | -0.9x+7.87=-0.7x+2.67 | | 6=2(x+7) | | 32x-6+5x=-23 | | -0.9x+7.87=0.7x+2.67 | | 6x-7=2x+7 |

Equations solver categories